2010
DOI: 10.1002/jso.21777
|View full text |Cite
|
Sign up to set email alerts
|

Using detection of survivin‐expressing circulating tumor cells in peripheral blood to predict tumor recurrence following curative resection of gastric cancer

Abstract: The detection of CTCs expressing survivin mRNA could be a good clinical biomarker used to predict the prognosis of patients with curatively resected gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 34 publications
1
41
0
1
Order By: Relevance
“…They reported that 3‐year DFS rates in patients who were positive or negative for survivin mRNA were 53.1% and 84.3%, respectively ( P  < 0.001). Furthermore, a multivariate analysis identified the status of survivin mRNA as an independent prognostic factor ( P  < 0.001) 32. In a study on 55 gastric cancer patients with stages I–IV, Yie et al .…”
Section: Prognostic Impact Of Ctcmentioning
confidence: 99%
See 3 more Smart Citations
“…They reported that 3‐year DFS rates in patients who were positive or negative for survivin mRNA were 53.1% and 84.3%, respectively ( P  < 0.001). Furthermore, a multivariate analysis identified the status of survivin mRNA as an independent prognostic factor ( P  < 0.001) 32. In a study on 55 gastric cancer patients with stages I–IV, Yie et al .…”
Section: Prognostic Impact Of Ctcmentioning
confidence: 99%
“…Recent studies reported the clinical utility of new molecular markers for RT‐PCR assays to detect CTC in the peripheral blood of patients with gastric cancer 37. Survivin has been attracting attention as a promising blood marker for CTC in gastric cancer 25, 26, 32. Survivin is a member of the inhibitor of apoptosis gene family and plays an important role in tumor progression 38.…”
Section: Detection Of Ctcmentioning
confidence: 99%
See 2 more Smart Citations
“…Even patients who present in the most favorable condition and who undergo curative surgical resection often die of recurrent disease (Duncavage et al, 2010;Dozois et al, 2011). Although preoperative tumor staging is useful to select the appropriate therapeutic strategy for GC patients, clinical tumor staging alone cannot predict patients' prognosis (Shimada et al, 2010;Cao et al, 2011;Feng et al, 2011). It has been reported that some immune-related biomarkers for diagnosis/prognosis and therapy monitoring of GC patients (Aburatani 2005;Tan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%